Method to Overcome Psychological Barriers in Students Learning the German Language - AKHMETOVA, A.ZH.; DALBERGENOVA, L.E.; MENLIBEKOVA, G.ZH.; DUJSENBINA, A.T.; TLEUBERDINA, G.T. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article studies the methods of dramatic performance aimed at the development of the learning and creative capacities of students in the process of learning the german language. The dramatic performance is based on the personality-oriented methods of the formation of communicative competence. The particular importance is given to the problem of psychological difficulties faced by students when learning the german language. The method of dramatic performance is proposed as an effective technique and tool for removing psychological barriers when learning the german language.RESUMEN Este artículo estudia los métodos de actuación dramática destinados al desarrollo del aprendizaje y las capacidades creativas de los estudiantes en el proceso de aprendizaje del idioma alemán. La actuación dramática se basa en los métodos orientados a la personalidad de la formación de la competencia comunicativa. Se le da especial importancia al problema de las dificultades psicológicas que enfrentan los estudiantes al aprender el idioma alemán. El método de actuación dramática se propone como una técnica y herramienta efectiva para eliminar las barreras psicológicas al aprender el idioma alemán.